A Forensic Responsibility: The Examination of Decision Making Strategies and Problem Solving Skills of Probation Officers - Erk, Mehmet Aykut; Fırat, Sunay (The Bulletin of Legal Medicine, 2020)
Introduction: Since working with the offenders that are in the probation process requires a detailed assessment, probation personnel should be able to produce logical solutions for the problems that may occur in the process. Probation personnel play a key role in whether the offenders are convicted or not. The fact that their decisions can influence the future of the offenders explains why they have such a key role in the probation process. Therefore, probation personnel have an important responsibility to fulfill since their decision can affect the judicial process of the offenders. This study was conducted to assess decision making strategies and problem-solving skills of the probation personnel working at the Probation Directorate of Adana. Methods: In this study, 83 personnel working for the Department of Probation constituted the sample group of this study, while 87 personnel working for other public institutions constituted the comparison group. Sociodemographic Data Form, Decision Strategies Scale (DSS) and Problem-Solving Inventory (PSI) were applied to the participants and the results were analyzed. Results: When the PSI total score and DSS sub-scale score averages of the sample group were compared to the comparison group, male probation personnel’s problem-solving skills total score and indecisiveness sub-scale point averages showed a statistically significant difference compared to the personnel from the comparison group. Similarly, a statistically significant difference was found between the married probation personnel and married comparison group personnel. ...